An update on ox-LDL-inducing vascular smooth muscle cell-derived foam cells in atherosclerosis - Guo, Jingjing; Du, Laijing (Frontiers in Cell and Developmental Biology, 2024)
Excess cholesterol accumulation induces the accumulation of foam cells, eventually accelerating atherosclerosis progress. Historically, the mechanisms of macrophage-derived foam cells have attracted attention because of their central role in plaque development, which was challenged by lineage tracing in union with single-cell sequencing (sc-seq). Accumulated studies have uncovered how vascular smooth muscle cells (VSMCs) proliferate and migrate to the vascular intima and accumulate, then transform into foam cells induced by surplus lipids, finally accounting for 30% to 70% of the total foam cells within the plaque of both mice and humans. Therefore, the mechanisms of VSMC-derived foam cells have received increasing attention. The review intends to summarize the transformation mechanism of VSMCs into foam cells induced by oxidized low-density lipoproteins (ox-LDL) in atherosclerosis.